The Effect of Autophagic Gene Inhibition on Exosomal Tau: A Therapeutic Target for Neurodegeneration - Yu, Philip (The Meducator, 2022)
Philip Yu is an undergraduate student researcher passionate about translational research in various fields. The following is an independent experimental study on genetic control of the cellular processes that regulate protein expression and transport in neurodegeneration. The study was conducted under the supervision of Dr. Derrick Gibbings in the Department of Cellular and Molecular Medicine at the University of Ottawa. Throughout the study, Philip conducted all experiments involved, in addition to collecting and processing the generated data. The misfolding of the protein tau contributes to the development of Alzheimer’s disease (AD). Misfolded tau is thought to propagate through a homeostatic degradation process known as autophagy, resulting in the export of cellular materials to the extracellular space via extracellular vesicles, called exosomes. By inhibiting the ATG7 and p62 genes necessary for autophagy to occur, the effects on the amount of exosomal and intracellular tau can be observed. Following the analysis of western blot and protein assay data, it was determined that the inhibition of the ATG7 and p62 genes results in a 70% and 60% reduction in the concentration of tau found in exosomes, respectively. These results suggest potential therapeutic applications of autophagic gene inhibition for the treatment of AD.